Probabilitas Modal Shift Model Angkutan Umum Di Bandara Adi Soemarmo Solo - Leliana, Arinda; Ependi, Ahmad; Fikria, Ainun (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2021)
Starting December 1, 2019, the Adi Soemarmo Solo Airport Train operates on the route Solo Balapan Station-Adi Soemarmo Airport, with a distance of 12.9 kilometers, and an average travel time of 20 minutes. The mobility of the movements can lead to the mode selection process. Mode selection is one of the models used in planning public transport transportation. The results of the calculation of the probability of displacement for the variable age and occupation of the respondent are variables that have a significant effect. After the final analysis was carried out with categorization for each variable age and occupation, the categories for each age (2) were obtained, namely 21-30 years old and age (3), namely 31-40 years old. For each category of significant work variables, namely the work of 1 student, the occupation of 3 BUMN, and the occupation of 4 private employees. The results of the probability calculation show that the older the respondent is, the probability has decreased as a person gets older, they will tend to prefer to use private vehicles because they are easier to move, safer, and faster than those who are younger and prefer to use public transportation. for mobility because it is more affordable and cheaper. Likewise with work, students / students have a higher probability than private and BUMN employees because their mobility intensity is not as frequent as private employees or BUMN.